Penyelesaian Sistem Persamaan Non-Linier Dengan Metode Perbaikan Regula Falsi Menggunakan Bahasa Pemrograman Javascript - ISTIQOMAH, FADILLAH (Jurnal Teknologi dan Bisnis, 2022)
Numerical method is a technique for solving mathematical problems with arithmetic operations. This method can solve problems where analytical calculations cannot be used. There are many types of numerical methods, one of which is the modified regula falsi method. This method is used to overcome the stagnation point case that occurs in the falsified regulation method. Solving non-linear equations with numerical methods can get results that are close to true (exact), because the calculations are done iteratively. In the numerical method there is an approximation solution or an approximation solution. The overlay solution is not the same as the true solution, so there is a difference between the two. This difference is called an error. Solutions with numerical methods always return a value in the form of a number.